Using EVA Method to Assess Achievement of BEJ Registered Retail Trade Company - Haryadi Sarjono (Bina Nusantara University, 2009)
This research aims to evaluate the the achievement in terms of the company finance, on whether it adds value or not to shareholders and investors) in generating profit on top of used capital or normally mentioned as the method of EVA. This research was carried out against 10 retail trade companies that registered in BEJ during the finance year of 2005 by using the documentary or secondary data obtained from the Centre of the Pasar Modal Reference (PRPM) in the Building of Bursa Efek Jakarta (BEJ). Evaluation results suggested 6 companies for future investment.